Between the assessment centre and reality: How and why biographical psychology makes human resource management more effective - Evgeny Rudnev (European Journal of Management and Business Economics (EJM&BE), 2022)
Purpose - The article makes a conceptual contribution to the substantiation of the foundations in personnel management for the development and decision-making in personnel assessment based on the biographical method. Design/methodology/approach - When substantiating the scientific direction, a comparative analysis, a comparison of the theoretical provisions of leadership and the methodology of personnel assessment, a critical appraisal of the assessment centre and biographical method were used. Findings - Modern science contains information about effective leadership and few grounds for objective selection for leadership positions. Why do some individuals become leaders in the churches, while others become leaders of business corporations? The accepted assessment tools allow obtaining information about the candidate, but do not have a scientific basis for making a decision about leadership in recruiting. Biographical psychology brings together leadership theories and assessment tools; it allows to establish a connection between developmental psychology, social, applied and organizational psychology and provides the integration of various directions in science. It allows a deeper understanding of the relationship between a person's biographical facts and his/her suitability in the profession to justify the reasons for leadership, as well as the grounds for selection for managerial positions. Originality/value - Substantiation of biographical psychology will allow in the future to legitimize the conduct of such studies, to come closer to the truth in the selection for leadership and not only positions, to understand the connection between the biography of leader and organizational culture. Biographical psychology will contribute to the creation of scientific basis for recruiting. To consider biographical factors more significantly (gender, age, sexual orientation, differences in personal development, and not just executive experience in the resume), this will reduce the economic costs of introducing and supporting costly procedures in organizations, as well as increasing the objectivity of the assessment and selection of personnel in organizations.
Keywords: 650; Assessment centre; Biographic method; Biographic psychology; Leadership; Recruiting